2016
DOI: 10.18632/aging.101126
|View full text |Cite
|
Sign up to set email alerts
|

Impaired energy metabolism of senescent muscle satellite cells is associated with oxidative modifications of glycolytic enzymes

Abstract: Accumulation of oxidized proteins is a hallmark of cellular and organismal aging. Adult muscle stem cell (or satellite cell) replication and differentiation is compromised with age contributing to sarcopenia. However, the molecular events related to satellite cell dysfunction during aging are not completely understood. In the present study we have addressed the potential impact of oxidatively modified proteins on the altered metabolism of senescent human satellite cells. By using a modified proteomics analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 53 publications
4
44
0
Order By: Relevance
“…Considering that senescence-associated aging affects cellular amino acid metabolism, this may provide an explanation for defective tryptophan catabolism by senescent MSCs. 4752 It has also been demonstrated that IDO in senescent MSCs undergo proteasomal degradation, which could additionally account for defective kynurenine production and associated impaired immune suppression. 53 Consistent with our previous study, we also show here that IL-10 expression is increased in macrophages cocultured with MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that senescence-associated aging affects cellular amino acid metabolism, this may provide an explanation for defective tryptophan catabolism by senescent MSCs. 4752 It has also been demonstrated that IDO in senescent MSCs undergo proteasomal degradation, which could additionally account for defective kynurenine production and associated impaired immune suppression. 53 Consistent with our previous study, we also show here that IL-10 expression is increased in macrophages cocultured with MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins were recently identified in a proteomic study demonstrating in WI‐38 human fibroblasts a strong interplay between replicative senescence, selenium, and selenoproteins, which are known to play a role in antioxidant defense and redox homeostasis . Of note, the restricted subsets of modified proteins in senescent fibroblasts and myoblasts are different, although an overlap of four proteins, involved in protein quality control, cellular morphology, and energy metabolism, was found for both cell types . In this paper, these findings are described and further discussed in view of the potential impact of oxidatively modified proteins on the altered metabolism of both senescent myoblasts and fibroblasts, with a specific focus on energy metabolism.…”
Section: Introductionmentioning
confidence: 84%
“…Immunodetection of carbonylated, HNE‐ and AGE‐ modified proteins was performed after 1‐DE and 2‐DE on young and senescent human WI‐38 fibroblasts and skeletal muscle satellite cells . Increased levels of these oxidative modifications were observed during replicative senescence in both cell types, encouraging the identification of the proteins targeted by these modifications and, hence, the potential mechanisms by which this accumulation of modified proteins could affect cellular functions.…”
Section: Protein Oxidative Modifications In Senescent Fibroblasts Andmentioning
confidence: 99%
See 2 more Smart Citations